ANALISIS FAKTOR PRODUKSI USAHATANI CABAI MERAH KERITING (Capsicum annum L.) DENGAN MENERAPKAN ATRAKTAN (Suatu Kasus di Kecamatan Pasirwangi Kabupaten Garut) - Tuti Karyani; Sumarno Tedi (Universitas Galuh Ciamis, 2021)
Curly red chili (Capsicum sp) is a horticultural commodity that is categorized as a commercial commodity, the main obstacle to red chili cultivation is pest attack, one type of pest that always arises and often destroys chili plants is fruit flies ((Bactrocera spp), but it can be controlled by The use of attractants, pest control using attractants is estimated to reduce production costs and ultimately increase farmers' income. The aim of this study was to analyze the production factors of the production of curly red chilies with and without using attractants in Garut Regency. This research was conducted in Pasirwangi District, Garut Regency, with a survey method on 72 curly red chili farmers. Data were analyzed using production function analysis The results showed that: Land area, seeds, urea fertilizer, Za fertilizer, KCl fertilizer, NPK fertilizer, organic fertilizer, pesticides and labor had an effect on products ii curly red chilies in Pasirwangi District, Garut Regency, the use of attractants affects the production of curly red chilies.